China and multilateralism : from estrangement to competition - Feng, Yuan, 1952- (Abingdon, Oxon ; New York, NY : Routledge, 2020)
"This book thoroughly analyzes China's political ideas regarding the international order and their reflection in China's engagement in multilateralism. It introduces the debates and discussions among Chinese intellectuals in international relation studies as an important part of non-western international relation theories, generating reflections on the convergences and divergences between China's political ideas and Europe-centric perspectives. With a focus specifically on China's main bilateral and multilateral relations in its principal regions of interest - East Asia and Central Asia - it also examines China's relationship with the United States, Russia and the European Union, and the One Belt Road initiative drawing on a mixture of primary and secondary Chinese language sources, extensive interviews with Chinese officials, academics and think tanks. This book will be of key interest to scholars and students of Chinese politics/studies, foreign policy analysis, Asian studies, and international relations"--
OCLC-licensed vendor bibliographic record.
Keywords: Geopolitics -- Asia; World politics -- 21st century; China -- Foreign relations -- 21st century; POLITICAL SCIENCE / General